2017
DOI: 10.23822/eurannaci.1764-1489.11
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in the treatment of anti-histamine refractory chronic spontaneous urticaria, randomized single-blinded placebo-controlled trial and an open label comparison study

Abstract: Summary Background. The management of anti-histamine refractory chronic spontaneous urticaria (CSU) has poorly defined therapeutic options. Some patients with CSU respond poorly to a fourfold increase in dosage of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
(10 reference statements)
0
24
0
3
Order By: Relevance
“…Thirty-six [ 28 – 34 , 36 , 38 40 , 42 46 , 48 50 , 53 55 , 57 – 63 , 67 – 71 , 73 , 76 , 78 ] of the 53 included studies, consisting of 4229 patients, reported SAEs. In the HCQ group, 2173 patients reported 55 SAEs, while in the control group, 2056 patients reported 38 SAEs.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six [ 28 – 34 , 36 , 38 40 , 42 46 , 48 50 , 53 55 , 57 – 63 , 67 – 71 , 73 , 76 , 78 ] of the 53 included studies, consisting of 4229 patients, reported SAEs. In the HCQ group, 2173 patients reported 55 SAEs, while in the control group, 2056 patients reported 38 SAEs.…”
Section: Resultsmentioning
confidence: 99%
“…The search process identified 713 articles, and a total of nine RCTs [10][11][12][13][14][15][16][17][18] were included after screening by title/abstract followed by full text review (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The characteristics of studies are summarized in Table 1, and the study quality assessment is summarized in Table 2. Eight RCTs were double-blind [11][12][13][14][15][16][17][18], and one was single-blind [10]. Only three RCTs were funded by drug companies [11,12,18].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Out of 92 studies included, eight were on COVID-19 [21][22][23][24][25][26][27][28], 13 studies were on malaria [29][30][31][32][33][34][35][36][37][38][39][40][41], 11 on other infectious conditions [42][43][44][45][46][47][48][49][50][51][52][53], 31 were on rheumatology , four on dermatologic diseases [85][86][87][88], eight on cancer [89][90][91][92][93][94][95][96], ve were on metabolic disease [97][98][99][100][101],...…”
Section: Study Characteristicsmentioning
confidence: 99%